2015
DOI: 10.1007/s00723-014-0639-y
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-Loaded Viral Capsids as Magnetic Resonance Imaging Contrast Agents

Abstract: Polymeric nanohybrid P22 virus capsids were used as templates for high density Gd3+ loading to explore magnetic field-dependent (0.5–7.0 T) proton relaxivity. The field-dependence of relaxivity by the spatially constrained Gd3+ in the capsids was similar when either the loading of the capsids or the concentration of capsids was varied. The ionic longitudinal relaxivity, r1, decreased from 25–32 mM−1 s−1 at 0.5 T to 6–10 mM−1 s−1 at 7 T. The ionic transverse relaxivity, r2, increased from 28–37 mM−1 s−1 at 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
0
23
1
Order By: Relevance
“…Macromolecule (such as protein)-based contrast agents are known to yield significantly higher r 1 relaxivity due to decreased local motion and increased correlation time 28 29 30 ; however in vivo applicable positive contrast agents, which maintain considerably enhanced r 1 relaxivity (>10 mM −1 s −1 ) with an acceptable r 1 / r 2 ratio (0.5 ~ 1) at high magnetic field (7 T), are a rarity 8 31 32 33 34 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macromolecule (such as protein)-based contrast agents are known to yield significantly higher r 1 relaxivity due to decreased local motion and increased correlation time 28 29 30 ; however in vivo applicable positive contrast agents, which maintain considerably enhanced r 1 relaxivity (>10 mM −1 s −1 ) with an acceptable r 1 / r 2 ratio (0.5 ~ 1) at high magnetic field (7 T), are a rarity 8 31 32 33 34 .…”
mentioning
confidence: 99%
“…The structural robustness and functional plasticity of AaLS make it an attractive candidate for a versatile bio- and nanotechnological platform 37 38 39 40 41 42 43 44 . Its hollow spherical architectures have been used as templates for the encapsulation of functional proteins 37 43 44 45 46 and the biomimetic synthesis of iron oxides 44 , as well as delivery vehicles of therapeutic and/or diagnostic reagents 32 34 . AaLS has also been engineered into multifunctional building blocks for fabricating uniform layer-by-layer (LbL) assemblies using non-covalent interactions between surface-displayed hexahistidine and Ni-NTA of AaLS 39 .…”
mentioning
confidence: 99%
“…It is noted from Table 6 that the estimated relaxation times are approximately three orders of magnitude smaller than the simulated estimate of 0.1 ns performed by Rast et al [ 12 ]. A reason for the discrepancy is most likely due to the high solution concentration effects enhancing the dipole-dipole interactions and as a result significantly decreasing the electronic relaxation times [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many viral systems have been engineered for biotechnology applications. For example, it has been demonstrated that CCMV and P22 can be modified to act as contrast agents for magnetic resonance imaging [44,45]. P22 has been further engineered to encapsulate a variety of exogenous proteins, including other viral proteins as a vaccine strategy [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%